ANALISIS PERTUMBUHAN EKONOMI, INVESTASI, DAN INFLASI DI INDONESIA - Silvia, Engla Desnim; Wardi, Yunia; Aimon, Hasdi (Program Studi Magister Ilmu Ekonomi, 2013)
ABSTRACT This article focused on analyze and determine the effect of (1) consumption, investment, government spending, net exports, and inflation to the economic growth in Indonesia. (2) government spending, money supply, interest rates, inflation and economic growth to investment in Indonesia. (3) government spending, money supply, and interest rates on inflation in Indonesia. The form of time series data from the first quarter of years 2000-the fourth quarter of years 2011. This study uses simultaneous equation model analysis tools with Two Stages Least Squared method (TSLS). The result of research concludes that (1) consumption, investment and net exports significantly affect economic growth in Indonesia. With the meaning of the word, when consumption, investment, and net exports increased then it will have an impact on economic growth in Indonesia. However, government spending and inflation does not significantly influence economic growth in Indonesia. (2) Government spending, interest rates, inflation and economic growth a significant effect on investment in Indonesia. This means that the increase in government spending, economic growth, lowerÂ interest rates and inflation will cause an increase to investment in Indonesia. However, the money supply has no significant effect on investment. (3) government spending, money supply, and interest rates significantly effect inflation in Indonesia. Â Keywords : Consumption, Government Spending, Net Exports, Money Supply, Interest Rates, Economic Growth, Investment, and Inflation